Peningkatan Hasil Belajar Matematika melalui Pembelajaran Matematika Realistik Siswa Kelas Vb SD Negeri 2 Sungai Raya - Lia Muliana; Riyanti Nurdiana; Muhammad Aqmal Nurcahyo (Jurnal Edukasi, 2023)
This study aims to improve Mathematics learning outcomes through Realistic Mathematics Learning in class VB students of State Elementary School 2 Sungai Raya. The learning outcomes used include cognitive learning outcomes and student attitudes during learning. This research is a classroom action research conducted collaboratively with the class teacher. This research design used a modified Kemmis & McTaggart model in 2 cycles consisting of planning, implementation, observation, and reflection. The object of the research was the learning outcomes of Mathematics through Realistic Mathematics Learning. Data collection techniques were testing and observation. Data analysis techniques were descriptive quantitative and qualitative. The results showed that the Mathematics learning outcomes of VB grade students of State Elementary School 2 Sungai Raya could improve after being given action through Realistic Mathematics Learning. In realistic Mathematics Learning used is to use real problems in life, use props, discuss results, and find concepts, then the teacher introduces standard procedures/formulas and relates other concepts in mathematics that are related. Students do not immediately get the formula but first students are directly involved in making observations using props and group discussions so that they find concepts. Initial cognitive learning outcomes showed that as many as 8 students (30%) had reached the KKM then in cycle I increased to 18 students (67%) and in cycle II increased to 23 students (85%). The average result of the attitude of cycle I reached 63% while cycle II obtained an average result of attitude of 81%. Thus, Realistic Mathematics Learning can improve the learning outcomes of mathematics students in class VB SD Negeri 2 Sungai Raya.